22nd IEEE VLSI Test Symposium, 2004. Proceedings.
DOI: 10.1109/vtest.2004.1299220
|View full text |Cite
|
Sign up to set email alerts
|

ELF-Murphy data on defects and test sets

Abstract: We at CRC have designed and LSI Logic has manufactured two test chip designs; these were used to investigate the characteristics of actual production defects and the effectiveness of various test techniques in detecting their presence. This paper presents a characterization of the defects that shows that very few defective chips act as if they had a single-stuck fault present and that most of the defects cause sequence-dependent behavior. A variety of techniques are used to reduce the size of test sets for dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Because of the many types of possible defects and the abstract nature of fault models, some defects will not be covered by, for example, a test with full stuck-at fault coverage. Defects that the test fails to cover are called test escapes [37,38,39,40]. To reduce test escape, different approaches exist, including the employment of a combination of more detailed fault models, application of a large (near exhaustive) test set, and N-detection.…”
Section: Fault Modellingmentioning
confidence: 99%
“…Because of the many types of possible defects and the abstract nature of fault models, some defects will not be covered by, for example, a test with full stuck-at fault coverage. Defects that the test fails to cover are called test escapes [37,38,39,40]. To reduce test escape, different approaches exist, including the employment of a combination of more detailed fault models, application of a large (near exhaustive) test set, and N-detection.…”
Section: Fault Modellingmentioning
confidence: 99%
“…Screening all defective chips is extremely difficult and expensive for such large chips; achieving 99% stuck-at fault coverage for a ten million gate chip means there are 200,000 uncovered stuck-at faults. In deep submicron technology, there are many defects that cannot be detected with existing fault models [3]. Even if a test technique is able to screen 100% of defective chips, good chips may become defective before their expected life spans due to accidents such as power surge and human mistakes.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that test sets obtained for the IRF model are considerably smaller than the TDF test sets while providing the same coverage of finite resistance interconnect open defects. The second type of open defects which are detected by two-pattern tests are intra-gate opens, which are modeled by TSOP faults. In recent years several studies [13,14,15] have revealed that a considerable number of defective chips exhibit sequence dependent but timing independent (SDTI) failures. Such failures can be symptomatic of intra-gate opens of infinite resistance (TSOP faults).…”
Section: Introductionmentioning
confidence: 99%